2013
DOI: 10.1111/resp.12085
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of peripheral endobronchial ultrasound with electromagnetic navigation bronchoscopy in peripheral lung nodules

Abstract: ENB improves localization of lung lesions after unsuccessful pEBUS but is often not sufficient to ensure confirmation of a specific diagnosis. Technical improvements in sampling methods could improve the diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
(35 reference statements)
7
38
1
1
Order By: Relevance
“…This is consistent with the only previously published study examining performance of EMN in patients in whom radial EBUS had failed to localise the lesion. CHEE et al [11] observed an improvement in visualisation from 75% to 93% with addition of EMN, but were only able to improve diagnostic yield by 7%, consistent with our findings. While EMN is a navigation tool, EBUS may be considered a localisation tool with visualisation of target PPLs confirming sampling is being performed from the exact site of interest.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the only previously published study examining performance of EMN in patients in whom radial EBUS had failed to localise the lesion. CHEE et al [11] observed an improvement in visualisation from 75% to 93% with addition of EMN, but were only able to improve diagnostic yield by 7%, consistent with our findings. While EMN is a navigation tool, EBUS may be considered a localisation tool with visualisation of target PPLs confirming sampling is being performed from the exact site of interest.…”
Section: Discussionsupporting
confidence: 82%
“…Isolated reports suggest combining the two techniques may achieve the highest diagnostic yields [7], although given EBUS achieves a sensitivity of 73% [2], and exceeding 84% in some reports [8][9][10], the cumulative gain seen following addition of EMN may not justify routine use of EMN consumables. Only one study has reported use of EMN only if peripheral lesions were unable to be localised with EBUS [11]. In that study, CHEE et al [11] described outcomes in 60 patients with a significant improvement in localisation rates, but no improvement in diagnostic yield.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This image-guided localization device could reportedly reach the peripheral lung lesions and obtain biopsy tissues (6,7). Thus far, however, the results, and ramifications of the benefits of ENB are still under debate (8). The accuracy and efficiency of ENB in the diagnosis of SPPLs has not been investigated in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein of how to continually improve our use of advanced bronchoscopic imaging, in this issue of Respirology, Chee et al 9 performed a prospective study aimed at predicting the factors associated with the need for combining pEBUS and NB and to determine what factors are associated with the 'gap' between localization and diagnosis of PPN. They were able to show that the majority of lesions were localizable using only the pEBUS, but that NB did improve this ability.…”
mentioning
confidence: 99%